Recurrent Severe Spasmophylia from Hypocalcaemia: A Case Report - Pinzon, Rizaldy Taslim; Sinaga, Ruth Vanessa Gloria (Fakultas Kedokteran Universitas Brawijaya, 2024)
Hypocalcemia can present with a variety of clinical symptoms and indications. In situations of nerve-related hypocalcemia, muscle cramps and tetany are signs of increased excitability in either peripheral nerves or the central nervous system. Here, we described the case of a 58-year-old woman experiencing ongoing pain and cramping in both her upper and lower extremities. Through careful physical, neurophysiological, and radiological examinations, we were able to identify hypocalcemia as the primary cause of her severe muscle spasms and cramps, known as spasmophilia. Further detailed history-taking revealed a past total thyroidectomy. Administration of adequate calcium supplementation successfully relieved the symptoms.